2004
DOI: 10.1002/ijc.20653
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intervention in prostate cancer patients: PSA response in a randomized double‐blind placebo‐controlled study

Abstract: The objective of this study was to show or to exclude an effect of dietary supplement on rising prostate-specific antigen (PSA) levels. We have studied the effect of a dietary supplement (verum, administered for 6 weeks) containing plant estrogens, antioxidants, including carotenoids, selenium and other putative prostate cancer inhibiting substances in a randomized placebo-controlled double-blind crossover study in 37 hormonally untreated men with prostate cancer and increasing PSA levels. Outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…29 Interestingly, a recent study examining the effect of a dietary supplement ('verum' -containing numerous potentially active compounds, including carotenoids, selenium and phyto-estrogens) in a group of patients not dissimilar to those included in this study describes a significant reduction in serum-free PSA but not in total PSA nor any increase in total PSA doubling times. 30 The period of supplementation was only 6 weeks; however, this was a randomized, doubleblind placebo-controlled study. 30 The clinical study described here reinforces the positive findings of these previous trials and demonstrates an ongoing and real effect upon serum PSA and perhaps therefore possibly on the behavior of established CaP in men receiving no other form of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Interestingly, a recent study examining the effect of a dietary supplement ('verum' -containing numerous potentially active compounds, including carotenoids, selenium and phyto-estrogens) in a group of patients not dissimilar to those included in this study describes a significant reduction in serum-free PSA but not in total PSA nor any increase in total PSA doubling times. 30 The period of supplementation was only 6 weeks; however, this was a randomized, doubleblind placebo-controlled study. 30 The clinical study described here reinforces the positive findings of these previous trials and demonstrates an ongoing and real effect upon serum PSA and perhaps therefore possibly on the behavior of established CaP in men receiving no other form of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…30 The period of supplementation was only 6 weeks; however, this was a randomized, doubleblind placebo-controlled study. 30 The clinical study described here reinforces the positive findings of these previous trials and demonstrates an ongoing and real effect upon serum PSA and perhaps therefore possibly on the behavior of established CaP in men receiving no other form of treatment. Indeed, while the overall effect was to demonstrate a statistically significant shallowing of the gradient of PSA, there was also a large increase in estimated PSA doubling time.…”
Section: Discussionmentioning
confidence: 99%
“…In Rotterdam, we have evaluated a strategy of parallel testing of new compounds using preclinical xenograft studies and experimental, PSA-based, short-term clinical phase II studies (Kranse et al, 2005;Schroder et al, 2005). The xenograft studies were used to confirm efficacy of the compound as well as to validate PSA as a surrogate biomarker for therapy response.…”
Section: Preclinical Psa Validation and Psa-based Phase II Trialsmentioning
confidence: 99%
“…Two randomised double-blind and placebo-controlled PSA-based phase II studies have been performed in Rotterdam with two different oral supplements constituted of several dietary nutrients including soy isoflavones, lycopene, selenium and antioxidants. Both studies showed prolongation of PSA doubling time when patients received the supplement, suggesting reduction in tumour progression (Kranse et al, 2005;Schroder et al, 2005). In a third preclinical study, the antitumour effect of two dietary nutrients, synthetic lycopene and vitamin E, was tested.…”
Section: Preclinical Psa Validation and Psa-based Phase II Trialsmentioning
confidence: 99%
“…It was proposed that the estrogen-like structure of isoflavones may interact with male steroid hormones and alter circulating sex hormone levels (Makela et al, 1991). A randomized double-blind intervention study of a dietary supplement containing soy isoflavones, phytosterols, and other nutrients noted a significant reduction in circulating testosterone, dihydrotestosterone (DHT), and free prostate-specific antigen (PSA) levels among prostate cancer patients (Kranse et al, 2005). An intervention with soy protein isolate showed significantly lower serum DHT levels and a decreased DHT/testosterone ratio at the end after a low soy and a high soy diet as compared to the control diet (Dillingham et al, 2005).…”
Section: Introductionmentioning
confidence: 99%